A condom uterine balloon device among referral facilities in Dar Es Salaam: an assessment of perceptions, barriers and facilitators one year after implementation - Oluwakemi Adegoke; Sandra Danso-Bamfo; Margaret Sheehy; Vincent Tarimo; Thomas F. Burke; Lorraine F. Garg (BMC Pregnancy and Childbirth, 2020)
Abstract Background Postpartum hemorrhage (PPH) is the leading cause of maternal death in Tanzania. The Every Second Matters for Mothers and Babies- Uterine Balloon Tamponade (ESM-UBT) device was developed to address this problem in women with atonic uterus. The objective of this study was to understand the barriers and facilitators to optimal use of the device, in Dar es Salaam Tanzania 1 year after implementation. Methods Semi-structured interviews of skilled-birth attendants were conducted between May and July 2017. Interviews were recorded, coded and analyzed for emergent themes. Results Among the participants, overall there was a positive perception of the ESM-UBT device. More than half of participants reported the device was readily available and more than 1/3 described ease and success with initial use. Barriers included fear and lack of refresher training. Finally, participants expressed a need for training and device availability at peripheral hospitals. Conclusion The implementation and progression to optimal use of the ESM-UBT device in Tanzania is quite complex. Ease of use and the prospect of saving a life/preserving fertility strongly promoted use while fear and lack of high-level buy-in hindered utilization of the device. A thorough understanding and investigation of these facilitators and barriers are required to increase uptake of the ESM-UBT device.